Analisis Miskonsepsi Mahasiswa Pendidikan Musik dalam Membaca Notasi Dasar - Fitri Indah Lestari; Aisyah Rahmadhani Hrp; Nindi Dwi Marsha; Tri Danu Satria; Lanang Riyadi (Journal of Music Science, Technology, and Industry, 2026)
Purpose: This study aims to analyze misconceptions of music education students in reading basic music notation, identify dominant types of misconceptions, and examine their pedagogical implications. Method: The research employed a descriptive-analytical approach with qualitative dominance supported by quantitative frequency analysis. The participants consisted of approximately 80 undergraduate students from various semesters. The research instrument included objective and essay tests designed to identify conceptual errors in duration, meter, pitch, rhythmic subdivision, symbol–sound relation, and classification of conceptual versus technical errors. Result and Discussion: The findings reveal that dominant misconceptions are related to meter interpretation, symbol–sound relations, and students’ inability to distinguish conceptual misunderstanding from technical mistakes. Misconceptions in basic note duration appear relatively lower compared to structural and semiotic aspects. These findings indicate that students’ difficulties in reading music notation are not merely technical but conceptual and structural in nature. Implication: The study recommends implementing a conceptual change-based instructional approach emphasizing metacognitive reflection and structural understanding in music notation learning.